The Growth Performance of Selected Spice Crops in Haryana State - Lal Choote; Kait Rohtas (Studia Ekonomiczne i Regionalne, 2021)
Subject and purpose of work: The study aims to evaluate the growth performance of spice crops in Haryana state of India.